Relationship Analysis between Socio-Economic Variables and Job Performance of Accredited Social Health Activists in Maharashtra - Kharole, Manjusha Manohar (Journal of Extension Education, 2021)
National Rural Health Mission (NRHM) was launched in India in 2005. It brought a new concept of Accredited Social Health Activist (ASHA) in to the arena of health sector of India. Since it is a new concept it is imperative to study the effect of socio economic variables on the job performance of ASHAs. Coefficient of correlation was applied to carry out the relational analysis between socio-economic variables and job performance of ASHAs. It was seen that age was positively related with job performance whereas all other independent variables were negatively and significantly related with job performance.